Participant engagement in a national longitudinal study of COVID-19: Insights from the INSPIRE study. - Kris Pui Kwan Ma; Tracy Stober; Michael Gottlieb; Rachel E Geyer; Kristin Rising; Sharon Saydah; Michelle Santangelo; Kristyn Gatling; Dylan Grau; Ralph C Wang; Juan Carlos Montoy; Ahamed Idris; et al. (PLoS ONE)
Objective To examine participants' motivations and their experiences throughout a decentralized, longitudinal COVID-19 study in the U.S. Methods We recruited 355 participants from the Innovative Support for Patients with SARS-CoV-2 Infections Registry (INSPIRE) between November 2022 - March 2023 to answer five qualitative survey questions anonymously. We used an inductive content analysis approach to analyze the data. Results We identified five key themes from the analysis, which reflected participants' a) motivations to join the study, b) study benefits, c) perceptions of survey questions, d) experiences with the research process, and e) preferences for disseminating research findings. Participants were motivated to learn with researchers about COVID-19. They expressed divided opinions about the relevance of INSPIRE research questions. They reported difficulties navigating the virtual research platform and the need for making survey participation less cognitively demanding. They sought more regular feedback on study findings. Conclusions Our findings offered insights into incorporating decentralized participatory methods in longitudinal research, strengthening reciprocal research communications, making virtual research platforms user-friendly, and employing strategies to reduce participants' cognitive burden in research. Policy implications Longitudinal studies should focus on optimizing these aspects of participant engagement to produce rigorous findings that inform policy and practice on lasting effects of COVID-19 including Long COVID.